Statistical distributions of ore elements in the Recsk ore field, Hungary - Ó. Kovács Lajos (Acta mineralogica-petrographica, 2006)
Statistical frequency distributions of the Ag, Au, Cu, Fe, Mo, Pb, S, Se and Zn contents measured in 51000 rock samples taken from 194 diamond boreholes exploring a large porphyry copper and polymetallic skam ore deposit-complex were analyzed. The distributions were represented by subsets of their common, and extreme values. The characteristic values of the ore components were displayed, and compared across units within three types of objects: spatial parts, rock-formations, and depth-zones of the deposit-complex. Among the deposit-parts, distributions of Ag, Cu, Pb, S and Au revealed significant differences. Except for a few units and those only in terms of several components, rock-formations exhibited a limited specialty in comparison. Statistically, values of the measured elements showed a notable vertical zoning.